2004
DOI: 10.1021/om049701l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Reactivity, and Computational Studies of the Cationic Tungsten Methyl Complex [W(NPh)(N2Npy)Me]+ and Related Compounds (N2Npy = MeC(2-C5H4N)(CH2NSiMe3)2)

Abstract: Me(L)] + (L ) MeCN (4 + ) or THF (5 + )). For comparison the neutral tantalum derivatives Ta(N t Bu)(N 2 N py )R (R ) Me (6) or η 1 -allyl (7)) were synthesized by reaction of Ta(N t Bu)(N 2 N py )Cl(py) with MeLi or (allyl)MgCl. Compound 6, valence isoelectronic with 2 + , was crystallographically characterized. Although both 2 + and 6 possess trigonal bipyramidal geometries at the metal, the methyl ligand in 2 + lies in the equatorial plane (with NPh trans to pyridyl), whereas in 6 the opposite arrangement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 95 publications
2
31
0
Order By: Relevance
“…The molecular structures of 14 and 15, as determined by X-ray crystallography, are shown in Figure 2 and selected distances and angles are given in Table 2. [5h,i, k, 17,19] However, more generally it has been found that five-coordinate compounds of this general type can have the NR ligand in either an equatorial position (e.g., [20] or an axial one (e.g.,…”
Section: Resultsmentioning
confidence: 99%
“…The molecular structures of 14 and 15, as determined by X-ray crystallography, are shown in Figure 2 and selected distances and angles are given in Table 2. [5h,i, k, 17,19] However, more generally it has been found that five-coordinate compounds of this general type can have the NR ligand in either an equatorial position (e.g., [20] or an axial one (e.g.,…”
Section: Resultsmentioning
confidence: 99%
“…The electronic preference is for the multiple bond to be oriented axially (termed the trans arrangement), as when it is oriented in the equatorial site (termed the cis arrangement), the π-donor components of the Ti−N imide triple bond compete more with the N amide lone pairs for π-acceptor orbitals on the metal center. 19 In compounds 9−11, steric demands clearly dominate, placing the borylimido ligand cis to the NMe donor. In all three structures, the boryl moiety is oriented such that the boryl ring lies nearly coplanar with the N(4)−Ti(1)−N(7) axis, this presumably being to avoid steric clash between the bulky Ar′ groups and the N 2 R N Me ligand substituents.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The positioning of the titanium–nitrogen multiple bond in such complexes depends on both steric and electronic considerations. The electronic preference is for the multiple bond to be oriented axially (termed the trans arrangement), as when it is oriented in the equatorial site (termed the cis arrangement), the π-donor components of the Ti–N imide triple bond compete more with the N amide lone pairs for π-acceptor orbitals on the metal center . In compounds 9 – 11 , steric demands clearly dominate, placing the borylimido ligand cis to the NMe donor.…”
Section: Resultsmentioning
confidence: 99%
“…This geometry is also predominantly maintained in solution according to NOE experiments. The hydrazide ligand in the solid‐state structure of 1 occupies the electronically preferred11 axial position trans to the NMe donor, whereas in I it lies exclusively in the equatorial position, which is the sterically preferred site. Minor resonances in the 1 H NMR spectrum of 1 are attributed to the isomer with NNPh 2 in the equatorial position.…”
Section: Methodsmentioning
confidence: 99%